The effect of blending sequence on the structure and properties of poly(vinyl chloride)/chicken eggshell powder composites. Issue 4 (29th July 2015) - Sharmeeni, M.; Munusamy, Y.; Ismail, H.
Abstract : The effect of the blending sequence of poly(vinyl chloride)/chicken eggshell powder (PVC/ESP) composites on the processing, mechanical properties, morphology, and thermal decomposition were investigated. The compounding of composites was done by using a Rheomix mixture internal mixer at 180°C and a rotor speed of 30 rpm for 10 min to allow the mixing torque to reach a steady state. The mechanical and morphological properties of PVC/ESP composites under different blending sequences have been characterized by a lightweight tensile tester and scanning electron microscopy. The thermal stability and thermal analysis of the composites were performed by thermogravimetric and differential scanning calorimetric analysis. Good interfacial adhesion between filler and matrix in composites prepared via blending sequence 2 has improved the tensile strength and thermal stability of the PVC/ESP composite compared with blending sequence 1 as proved from scanning electron microscopy results on the tensile fracture surface of the composites. Thermogravimetric analysis results show that blending sequence 2 exhibited higher thermal stability comparable with blending sequence 1. In addition, the differential scanning calorimetric analysis results illustrate that the composites prepared via blending sequence 2 exhibit higher melting and crystallization temperature values compared with composites prepared via blending sequence 1. J. VINYL ADDIT. TECHNOL., 23:298–304, 2017. © 2015 Society of Plastics Engineers